EFL Students’ Perceptions Toward the Use of TikTok Trending English Songs in Vocabulary Learning - Sheryn Salsabilla; Widya Caterine Perdhani (Universitas Islam Negeri Palopo, 2025)
This study examines senior high school EFL students' experiences and perceptions of incidental vocabulary acquisition through English songs on TikTok. Using a qualitative descriptive design with a phenomenological approach, the research was conducted at SMA Shalahuddin, Malang, with three purposively selected students from grades X-XII. Data were collected through semi-structured interviews and supporting documentation, such as TikTok screenshots and lyric displays, and analyzed thematically using Miles and Huberman’s interactive model. The findings indicate that English songs on Tik Tok provide meaningful extensive listening input through repeated, algorithm-driven exposure, which supports incidental vocabulary learning. Students often replayed songs due to enjoyment, emotional engagement, and personal relevance, facilitating the acquisition of pronunciation, slang, and contextual expressions. They also showed self-directed learning behaviors, including using translation tools and consulting peers or family members. Although distractions sometimes reduced concentration, students consistently perceived Tik Tok songs as beneficial for vocabulary development. Overall, TikTok functions as an effective informal learning environment for vocabulary acquisition, though the small sample size limits generalizability and calls for further research with broader participants.